Short and Medium Chain Fatty Acids and Their Derivatives as a Natural Strategy in the Control of Necrotic Enteritis and Microbial Homeostasis in Broiler Chickens - Gomez-Osorio, Luis-Miguel; Yepes-Medina, Veronica; Ballou, Anne; Parini, Manuela; Angel, Roselina (Frontiers in Veterinary Science, 2021)
The use of antibiotic growth promoters (AGPs) has historically been the most important prophylactic strategy for the control of Necrotic Enteritis (NE) caused by some Clostridium perfringens toxin types in poultry. During the last five decades, AGPs have also been supplemented in feed to improve body weight gain and feed efficiency as well as to modulate the microbiome (consisting of microbes and their genes both beneficial and potentially harmful) and reduce enteric pathogens, among other benefits. New regulatory requirements and changes in and consumer preferences have contributed to generate new animal welfare regulations. The need to balance cost, productivity, food safety and welfare has generated new challenges for the poultry industry. This has led to strong interest in natural alternatives to the AGPs for the prevention and control of illnesses caused by enteric pathogens., This interest is not just not focused just on the direct removal or inhibition of the causative microorganisms but also the improvement of intestinal health and homeostasis using a range of feed additives. A group of promising feed additives is short- and medium-chain fatty acids (SCFA and MCFA, respectively) and their derivatives. The use of SCFA and MCFA, including succinicbutyric, caproic, caprylic, capric and lauric acids, valeric and butyric acid has shown strong effects against NE in broilers both at experimental and commercial levels., in These fatty acids also addition to benefits as intestinal health integrity and intestinal homeostasis. Other effects have also been documented, including increases in intestinal angiogenesis and gene expression of tight junctions. Chemical modifications to improve stability and point of release in the intestine have been shown to improve the efficacy of SCFA and MCFA and their derivatives. The aim of this review is to give an overview of SCFA, MCFA and their derivatives, as an alternative to replace AGPs to control the incidence and severity of NE in poultry.